Peran Guru Fikih Dalam Meningkatkan Kesadaran Ibadah Shalat Zuhur Berjamaah Peserta Didik Kelas VII di MTSS Darul Makmur Sungai Cubadak Kecamatan Baso - Sutra, Dewi Rona; D, Deswalantri; Gustina, Hutri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Education has a very important role in creating human survival. Education is also a process to improve human dignity, for this reason humans need to be guided so that they are able to develop themselves to become perfect human beings, in the sense of humans who have faith and are devoted to Allah SWT, have noble character, and have knowledge and skills, a stable personality and independent, this research is included in field research which is a case study with a descriptive qualitative approach method. Implementation of Fiqh Learning. In the implementation of fiqh learning, several things are discussed, including fiqh teaching materials, fiqh learning design, fiqh learning methods, fiqh learning media and evaluation of fiqh learning 2. Improving Students' Awareness of Worship in Performing Fardhu Prayers. There are several ways that can be done to instill faith or increase students' devotion to worship, namely, providing examples or teaching, familiarizing (of course with good ones) (1) material focused on fardhu prayers, learning design using the Ministry of Religion reference , learning methods using lecture methods, intensification, learning media using audio-visual and learning evaluation using tests. (2) enforce discipline. (3) students lack discipline, teachers are active while students are passive. (4) Supporting factors: awareness of the students themselves, the existence of facilities that support worship. Meanwhile, inhibiting factors: student motivation and lack of discipline.